2017
DOI: 10.1021/acs.jpca.7b09873
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the CH3 + C5H5 Reaction: A Theoretical Study

Abstract: Formation of fulvene and benzene through the reaction of cyclopentadienyl (CH) with methyl radical (CH) and consequent dissociation of its primary CH products has been studied using ab initio and theoretical kinetics calculations. The potential energies and geometries of all involved species have been computed at the CCSD(T)-F12/cc-pVTZ-f12//B2PLYPD3/aug-cc-pVDZ level theory. Multichannel/multiwell RRKM-Master Equation calculations have been utilized to produce phenomenological pressure- and temperature-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Based on their simulations using reaction rate constants computed at the high pressure limit employing transition state (TS) theory, the authors concluded that such a mechanism could contribute to the formation of pyrene from cyclopenta­[ d , e , f ]­phenanthrene, but its role in the presence of other competing PAH mechanisms still needs to be determined. A similar mechanism is also well known from theoretical studies on the formation of benzene in the cyclopentadienyl C 5 H 5 + CH 3 reaction and of naphthalene in the indenyl C 9 H 7 + CH 3 reaction; the latter has been recently confirmed experimentally in a pyrolytic chemical micro reactor with the product detection by means of photoionization mass spectrometry …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Based on their simulations using reaction rate constants computed at the high pressure limit employing transition state (TS) theory, the authors concluded that such a mechanism could contribute to the formation of pyrene from cyclopenta­[ d , e , f ]­phenanthrene, but its role in the presence of other competing PAH mechanisms still needs to be determined. A similar mechanism is also well known from theoretical studies on the formation of benzene in the cyclopentadienyl C 5 H 5 + CH 3 reaction and of naphthalene in the indenyl C 9 H 7 + CH 3 reaction; the latter has been recently confirmed experimentally in a pyrolytic chemical micro reactor with the product detection by means of photoionization mass spectrometry …”
Section: Introductionsupporting
confidence: 61%
“…Alternatively, the five-membered ring in R1 can be converted to a six-membered ring via the MAC mechanism involving methyl radical addition to the radical site, followed by a H loss, CH 2 insertion into a C–C in the five-membered ring, elimination of another H-atom, and aromatization, R1 + CH 3 → pyrene + 2H. Because of the structural and mechanistic similarity, the rate constant for the overall process is anticipated to be similar to that for the C 5 H 5 + CH 3 → C 6 H 6 + 2H reaction, 2.5 × 10 12 cm 3 mol –1 s –1 at 1500 K and 1 atm, that is, ∼300 times higher than that for R2 + C 2 H 2 → 1-pyrenylmethyl + H. The R1 + CH 3 reaction is likely to be somewhat slower than C 5 H 5 + CH 3 due to a different degree of electron delocalization and steric constraints caused by the additional presence of the six-member rings in R1. Therefore, a more quantitative conclusion about the competition of R1 + CH 3 and R2 + C 2 H 2 can be made only after the kinetics of R1 + CH 3 is characterized and a fuller kinetic modeling involving all significant competing reactions is carried out.…”
Section: Discussionmentioning
confidence: 99%
“…1). Although the formation of naphthalene via recombination of two cyclopentadienyl radicals (C 5 H 5 • ) 20,21 and methylation of indenyl has been predicted theoretically 22,23 , similar to the formation of benzene via methylation of the cyclopentadienyl radical 2426 , the validity of elementary reactions between free hydrocarbon radicals leading to PAHs at high temperatures have not been realized experimentally. Indeed there is no experiment to date under high temperature conditions that has followed the kinetics and mechanism of a hydrocarbon free radical with a second hydrocarbon radical, and hence the reaction route through methylation of the indenyl radical provides a benchmark for the conversion of a five-membered ring to a six-membered ring in PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions between two hydrocarbon radicals such as propargyl (C 3 H 3 )-propargyl (C 3 H 3 ), methyl (CH 3 )-cyclopentadienyl (C 5 H 5 ), and cyclopentadienyl (C 5 H 5 )-cyclopentadienyl (C 5 H 5 ) , have been suggested to lead to aromatic systems such as benzene (C 6 H 6 ) and naphthalene (C 10 H 8 ), respectively. However, the validity of elementary reactions between free hydrocarbon radicals leading to aromatic hydrocarbons at high temperatures have been scarce under well-defined experimental conditions in molecular beams.…”
Section: Molecular Mass Growth Mechanismsmentioning
confidence: 99%